Treatments for Burning Mouth Syndrome: A Network Meta-analysis. (February 2023) - Alvarenga-Brant, R.; Costa, F.O.; Mattos-Pereira, G.; Esteves-Lima, R.P.; Belém, F.V.; Lai, H.; Ge, L.; Gomez, R.S.; Martins, C.C.
The aim of this systematic review and network meta-analysis (NMA) of randomized controlled trials was to evaluate the effectiveness of treatments for pain relief of burning mouth syndrome (BMS). Five databases and gray literature were searched. Independent reviewers selected studies, extracted data, and assessed the risk of bias. The primary outcome was pain relief or burning sensation, and the secondary outcomes were side effects, quality of life, salivary flow, and TNF-α and interleukin 6 levels. Four comparable interventions were grouped into different network geometries to ensure the transitivity assumption for pain: photobiomodulation therapy, alpha-lipoic acid, phytotherapics, and anxiolytics/antidepressants. Mean difference (MD) and 95% CI were calculated for continuous outcomes. The minimal important difference to consider a therapy beneficial against placebo was an MD of at least −1 for relief of pain. To interpret the results, the GRADE approach for NMA was used with a minimally contextualized framework and the magnitude of the effect. Forty-four trials were included (24 in the NMA). The anxiolytic (clonazepam) probably reduces the pain of BMS when compared with placebo (MD, −1.88; 95% CI, −2.61 to −1.16; moderate certainty). Photobiomodulation therapy (MD, −1.90; 95% CI, −3.58 to −0.21) and pregabalin (MD, −2.40; 95% CI, −3.49 to −1.32) achieved the minimal important difference of a beneficial effect with low or very low certainty. Among all tested treatments, only clonazepam is likely to reduce the pain of BMS when compared with placebo. The majority of the other treatments had low and very low certainty, mainly due to imprecision, indirectness, and intransitivity. More randomized controlled trials comparing treatments against placebo are encouraged to confirm the evidence and test possible alternative treatments (PROSPERO CRD42021255039).